Post-anthesis Relationships Between Nitrogen Isotope Discrimination and Yield of Spring Wheat Under Different Nitrogen Levels - Effah, Zechariah; Li, Lingling; Xie, Junhong; Karikari, Benjamin; Wang, Jinbin; Zeng, Min; Wang, Linlin; Boamah, Solomon; Padma Shanthi, Jagadabhi (Frontiers in Plant Science, 2022)
Wheat grain yield and nitrogen (N) content are influenced by the amount of N remobilized to the grain, together with pre-anthesis and post-anthesis N uptake. Isotopic techniques in farmed areas may provide insight into the mechanism underlying the N cycle. 15N-labeled urea was applied to micro-plots within five different fertilized treatments 0 kg ha-1 (N1), 52.5 kg ha-1 (N2), 105 kg ha-1 (N3), 157.5 kg ha-1 (N4), and 210 kg ha-1 (N5) of a long-term field trial (2003–2021) in a rainfed wheat field in the semi-arid loess Plateau, China, to determine post-anthesis N uptake and remobilization into the grain, as well as the variability of 15N enrichment in aboveground parts. Total N uptake was between 7.88–29.27 kg ha–1 for straw and 41.85–95.27 kg ha–1 for grain. In comparison to N1, N fertilization increased straw and grain N uptake by 73.1 and 56.1%, respectively. Nitrogen use efficiency (NUE) and harvest index were altered by N application rates. The average NUE at maturity was 19.9 % in 2020 and 20.01 % in 2021, however, it was usually higher under the control and low N conditions. The amount of 15N excess increased as the N rate increased: N5 had the highest 15N excess at the maturity stage in the upper (2.28±0.36 %), the middle (1.77±0.28 %) and the lower portion (1.68± 1.01 %). Compared to N1, N fertilization (N2-N5) increased 15N excess in the various shoot portions by 50, 38, and 35% at maturity for upper, middle and lower, portions respectively. At maturity, the 15N excess remobilized to the grain under N1-N5 was between 5 to 8%. Our findings revealed that N had a significant impact on yield and N isotope discrimination in spring wheat that these two parameters can interact, and that future research on the relationship between yield and N isotope discrimination in spring wheat should take these factors into account.